2020
DOI: 10.1021/acs.chemmater.0c03831
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Hybrid Passivation Strategy for Ultrastable Photoluminescence Perovskite Nanocrystals

Abstract: Perovskite nanocrystals (NCs) are promising lightemitting materials for next-generation illuminations and displays. The main challenge for practical applications is to achieve high durability. Herein, a hybrid passivation strategy was developed to simultaneously enhance the photoluminescence quantum yield (PLQY) and the stability of perovskite CsPbBr 3 NCs by two-step modification with surface halogen replenishment and atomic layer deposition. The hybrid passivation mechanisms regarding the repairing of NCs' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 61 publications
0
48
0
Order By: Relevance
“…5 (b)The photo stability of CsPbBr3 NCs by two-step hybrid passivation strategy. 6 Reprinted (adapted) with permission from (COMPLETE REFERENCE CITATION). Copyright (YEAR) American Chemical Society.…”
Section: Figure 1 (A)mentioning
confidence: 99%
See 2 more Smart Citations
“…5 (b)The photo stability of CsPbBr3 NCs by two-step hybrid passivation strategy. 6 Reprinted (adapted) with permission from (COMPLETE REFERENCE CITATION). Copyright (YEAR) American Chemical Society.…”
Section: Figure 1 (A)mentioning
confidence: 99%
“…Copyright (YEAR) American Chemical Society. 5,6 At present, researches on quantum dot materials based on atomic layer deposition technology are mainly divided into three categories: 1. ALD technology was used to coat and modify the surface to obtain high quality photoluminescence and electroluminescence thin film luminescence layer.…”
Section: Figure 1 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these developments, little research has investigated the complex interplay between macro and micro‐scale optoelectronic behavior of perovskite‐PV devices for indoor applications, which is crucial to enhance their performance. This understanding can be achieved by performing macroscopic optical measurements, e.g., current‐voltage [ 5 ] and photoluminance, [ 6 ] in conjunction with scanning probe microscopy (SPM) with high spatial resolution, [ 7 ] such as conductive atomic force microscopy (c‐AFM), [ 8 ] which maps electronic transport capability, [ 9 ] ion migration, [ 10 ] surface hysteresis, [ 11 ] ferroelectric polarization, [ 12 ] and face orientation of PSCs. [ 11,13 ] In addition to c‐AFM, Kelvin probe force microscopy (KPFM) has been implemented to evaluate the device performance [ 14 ] and to gain an improved understanding of the local charge carrier movement mechanism, which includes charge carrier generation, [ 15 ] accumulation, [ 16 ] recombination, [ 17 ] transport, [ 18 ] relaxation, [ 19 ] and extraction at the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Besides, the pinhole-free films with high densification could be obtained with low-temperature ALD process. [19] Thus, ALD-based encapsulation structures have been developed to be applied to the flexible displays. [20][21][22] As for the inorganic barriers, Choi et al revealed that with the thickening of the barrier layer, the WVTR value would decrease and saturate at a specific thickness.…”
mentioning
confidence: 99%